An Analysis Basic Strategy of Verbal Humor found In Ellen DeGeneres Monologue Season 17,2019 : Pragmatic Approach study - Alvina faula (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Abstract : Language is not only a means of communication between humans; however, it can convey funny expressions known as humor. Everyone likes something fun and funny. In entertainment, humor has developed; thus, physically offensive humor decreases and proceeds to verbal humor, especially on talk shows. As one of America's famous comedy talk shows, Ellen DeGeneres Talkshow successfully maintains its fame and verbal humor. Using a Pragmatic context approach, this study uses the theory of Victor Raskin's Three Major Elements of Humor, which consists of Incongruity, Superiority, and Release/Relief. This study aims to determine the types of humor elements that influential in Ellen Monologue Season 17, 2019, entitled